Politics and imagination : Soviet children's culture and the space age, 1957-1964 - Trowel, K (2003)
As the first man-made satellite orbited the Earth in October 1957, radios worldwide transmitted its persistent signal. Sputnik’s pulsing beep was either the most exhilarating proof to date of man’s rapid technological development, or a haunting reminder that, in the bi-polar world, science and technology had become the yardstick by which ideological battles were won or lost. For some the incessant tone represented the triumph of Soviet socialism. For others, it meant a new and harrowing challenge to Western democracy and capitalism. Though these perspectives were, in fact, inseparable, each represented a quantitatively different world view in the ideologically contentious atmosphere of the Cold War. Regardless of where one stood in this polemic, Sputnik represented the first foray into a realm previously explored only in works and dreams of scientific and literary visionaries. The emergence of the space age in the middle of the twentieth century had an enormous impact on virtually every sphere of international life. Sputnik was the ‘shot’ that set thousands of scientists, millions of rubles (and dollars), and a seemingly endless stream of propaganda in motion, from both East and West. The early years of the Soviet space program offer an interesting and important perspective on Soviet history precisely because of this massive mobilization of resources. No group, from the most exalted party apparatchik to the lowest kolkhoz worker (and such class distinctions were well entrenched and problematic for the Khrushchev regime, as chapter 3 will discuss) was immune from Sputnik’s influence. This paper seeks to explore the influence of this epoch-defining event on a group whose members were not defined primarily by class affiliation or profession but rather by age: Soviet children. Continued in thesis ...